analisis ketercapaian produktivitas Bauxite Ore Getting terhadap produktivitas Bauxite Processing Plant PT. Jaga Usaha Sandai (PT. JUS) site sandai, Kecamtan Sandai, Kab Ketapang, Kalimantan Barat - Fuji Kurniansyah; Tri Gamela Saldy (Departemen Teknik Pertambangan FT UNP, 2022)
PT. Jaga Usaha Sandai (PT. JUS) is one of the contracting companies in the field of Bauxite Mining located in Sandai District, Ketapang Regency, West Kalimantan Province. Mining process at PT. Jaga Usaha Sandai, one front loading using 1 unit of Excavator to serve 8 units of Dump Truck and 1 washing plant tool to wash bauxite material. PT. Jaga Usaha Sandai has a target of 300,000 MT / month, and for each washing plant as much as 75,000 MT / month. While the realization of production reached in October amounted to 246,554.09 MT, it can be said that it has not achieved the production target. After analysis and repair efforts were obtained production on the digging tool loaded 490.43 Tons / hour, the conveyance became 45.06 Tons / hour and bauxite processing plant to 357.19 Tons / hour. And the effective working hours of the digging tool loaded by 83%, the conveyance of 84%, and bauxite processing plant to 84%.